Biological characterization of dehydrated amniotic membrane allograft: Mechanisms of action and implications for wound care. Issue 8 (26th May 2020) - Moore, Marc C.; Bonvallet, Paul P.; Damaraju, Sita M.; Modi, Heli N.; Gandhi, Ankur; McFetridge, Peter S.
Abstract: There is a growing clinical demand in the wound care market to treat chronic wounds such as diabetic foot ulcers. Advanced cell and tissue‐based products (CTPs) are often used to address challenging chronic wounds where healing has stalled. These products contain active biologics such as growth factors and cytokines as well as structural components that support and stimulate cell growth and assist in tissue regeneration. This study addresses the in vitro biologic effects of a clinically available dehydrated amniotic membrane allograft (DAMA). The broad mechanism of action results from DAMA's biologic composition that leads to stimulation of cell migration cell proliferation, and reduction of pro‐inflammatory cytokines. Results show that DAMA possesses growth factors and cytokines such as EGF, FGF, PDGFs, VEGF, TGF‐β, IL‐8, and TIMPs 1 and 2. Furthermore, in vitro experiments demonstrate that DAMA stimulates cell proliferation, cell migration, secretion of collagen type I, and the reduction of pro‐inflammatory cytokines IL‐1β, IL‐6, and TNF‐α. This study findings are consistent with the clinical benefits previously published for DAMA and other CTPs in chronic wounds suggesting that the introduction of DAMA to non‐healing, complex wounds helps to improve the wound milieu by providing essential structural components, cytokines, and growth factors to create an appropriate environment for wound healing.